DAMPAK CELEBRITY ENDORSER DAN IKLAN TERHADAP MINAT BELI KONSUMEN HONDA BEAT - Sahidillah Nurdin (Jurnal Co Management, 2019)
This Research aims to determine and describe The Impact of Celebrity Endorser and Advertising to Purchase Intention Honda Beat in PT. Daya Anugerah Mandiri which starred by Al-Ghazali and JKT48. The type of this research is explanatory research with quantitative approach. The population ini this research is the consumer of PT. Daya Anugerah Mandiri. The sample in this research area 100 respondents chosen with insidental sampling and data collection method using questionnaires. Analysis of data use descriptive analysis and multiple linear regression analysis. The result of multiple linear regression analysis jointly show that both variables Celebrity Endorser & Advertising have significant influance toward Purchase Intention